Sectarianism at workplace in Gilgit - Ullah, Mehfooz; Ali, Zaigham (Taylor & Francis, 2019)
This paper is part of a broader research that was carried out to explore and determine the scope and nature of sectarianism as perceived and experienced by employees in their workplaces in Gilgit-Baltistan. This region has experienced intense sectarian strife over last two decades, claiming hundreds of lives in the process. The region’s capital city Gilgit in particular has seen violent clashes between the two major sects of Islam – Sunni and Shi’a .Using the framework of organizational theory with a specific focus on the concept of informal organizations, this research attempts to provide empirical evidence of the existence and manifestation of sectarianism at the workplace in Gilgit city. Main themes that emerged from the qualitative interviews conducted with employees working in public sector organizations included; prevalence of sectarianism, nature of sectarianism, and the balance formula. Preliminary findings suggested that sectarianism did exist in the selected organizations operating in Gilgit. The sectarianism in public institutions have posed challenges in terms of the governance and administration of the province. This issue has also found traction in the debate surrounding constitutional rights as the two major sects – Sunni and Shi’a – foresee the governance models of Gilgit-Baltistan through a sectarian-tinted lens.